Recycling cigarette butts in lightweight fired clay bricks - A. Kadir, Aeslina; Mohajerani, Abbas (ICE Publishing, 2011)
Several trillion cigarettes are produced worldwide annually, resulting in tonnes of cigarette butt waste. Cigarette butts accumulate in the environment due to the poor biodegradability of the cellulose acetate filters. Results from a study on recycling cigarette butts into fired clay bricks are presented. Five different soil–cigarette butts mixes with different percentages of cigarette butts were used. The physico-mechanical properties of manufactured bricks including compressive strength, flexural strength, density, water absorption and thermal conductivity are discussed. The results show that the density of fired bricks was reduced significantly, by up to 30%, depending on the percentage of cigarette butts incorporated into the raw materials. Similarly, the compressive strength of bricks decreased according to the percentage of cigarette butts included in the mix, and the estimated values of thermal conductivity were also reduced significantly. The results also show that the mixing time has a considerable effect on the properties of the fired clay bricks tested. Furthermore, the leachate test results revealed only trace amounts of heavy metals. It was concluded that cigarette butts can be regarded as a potential addition to the raw materials used in the manufacture of lightweight fired bricks and, furthermore, that recycling cigarette butts in bricks is a very practical and potentially significant contribution in terms of a sustainable solution to one of the serious environmental pollution problems in the world.